CONSEQUENCES OF THE COVID-PANDEMIC FOR THE DEVELOPMENT OF ENTREPRENEURIAL ACTIVITY AND INTERNATIONAL BUSINESS IN UKRAINE - Хаустова, Євгенія; Сова, Роман (Journal of Strategic Economic Research, 2022)
The article is devoted to the features of entrepreneurial activity and international business in the conditions of crisis and COVID-pandemic. In particular, the common features and differences between the crisis caused by the COVID-pandemic and most economic recessions, typical of the global economic space have been established. The analysis of the main indicators of the activity of subjects of large, medium, small and microenterprises is carried out. The dynamics of the volumes of top export and import products in the conditions of a pandemic is studied, the actual problems of the organization of economic activity of enterprises in the field of international business are identified. The study of the peculiarities of entrepreneurial activity in the conditions of the COVID-19 pandemic allowed us to identify the following risks and threats: partial or complete shutdown of activities; reduction of liquidity; reduction in the structure of consumer demand; loss of channels and the domestic sales market; uncertainty of the situation in the foreign market regarding the restoration of the timing and volume of exports. The hypothesis of the study is the statement that changes in the structure of international trade and trends in the reduction of exports and imports of products are rapidly increasing the competition of international business, and, therefore, require new foreign trade strategies from enterprises. Due to the fact that the COVID-pandemic is an international problem, the analysis of the activities of enterprises in the sphere of international business takes into account global changes in trade. It is proved that the analysis carried out in the article has practical and theoretical significance for domestic enterprises, since the proposed measures to overcome the negative consequences as a result of the pandemic are aimed at a rapid response from enterprises. Since both domestic and foreign trade of our state have found in the difficult conditions, the article presents the main factors for the development of international business in a pandemic at the national level, and also considers the possibilities of improving the financial and economic condition of enterprises through innovations and flexible pricing policy, export support in the form of grants; changes in the current legislation in the field of export-import operations. In the process of writing the article, such methods as: analysis and synthesis; deductive method and induction method; graphical method; comparison method were used.